Characterization of Lactobacillus spp. as Probiotic and Antidiabetic Potential Isolated from Boza, Traditional Fermented Beverage in Turkey - Chandana Kumari V. B.; Sujay Huligere; Jayanthi M. K.; Khang Wen Goh; Sudhanva M. Desai; Kalabharthi H. L.; Ramith Ramu (International Journal of Microbiology)
Boza, a cereal-based beverage popular in southeast Europe, is fortified with probiotics and is believed to positively impact the composition of the gut microflora. This investigation focused on fermented cereal-based beverage boza to identify strains of probiotic Lactobacillus spp. capable of inhibiting carbohydrate-hydrolysing enzymes α-glucosidase (AG) and α-amylase (AA). The isolated bacterial strains underwent a comprehensive assessment, including biochemical, molecular, and probiotic trait analyses such as tolerance survivability, adhesion, safety, and health-promoting attributes. We evaluated the inhibitory potential of the supernatant, cell lysate, and intact cells of Lactobacillus spp. Molecular analysis has revealed that isolates RAMULAB30 and RAMULAB29 exhibit a significant genetic similarity (>97%) to Lacticaseibacillus paracasei and Limosilactobacillus fermentum, respectively. These findings are documented in the NCBI database. They exhibited significant resistance to gastrointestinal and intestinal fluids, also indicating their potential for adhesion. Additionally, the isolates showed a significant antibacterial activity, particularly against Micrococcus luteus. They showed resistance to vancomycin and methicillin antibiotics but were more susceptible to streptomycin and ampicillin. Furthermore, the strains demonstrated antioxidant properties. To ensure their safety, a haemolytic assay was conducted despite their general recognition as safe (GRAS) status. The study primarily aimed to evaluate the inhibitory effects of the extract on enzymes AG and AA. Bacterial isolates demonstrated a significant inhibitory activity against both enzyme AG (32%–67% inhibition) and enzyme AA (18%–46% inhibition) in different forms, including supernatant (CS), lysed extract (CE), and intact cell (IC). These findings underscore the potential of bacterial isolates to inhibit the enzyme activity effectively. Furthermore, the L. fermentum RAMULAB29 and L. paracasei RAMULAB30 strains exhibit remarkable antidiabetic potential. Food products incorporating these strains have promising prospects as nutraceuticals, providing improved health benefits.